‘Rapid Counseling’ with Single-Session Music Therapy: A Modern Approach to Boosting the Academic Self-Efficacy of Today’s Generation - Lara, Lara; Oentarto, Aloysius Selo Aryobimo; Situmorang, Dominikus David Biondi (Buletin Konseling Inovatif, 2025)
As a new student, it is a big challenge for everyone. As an individual, it is very important to have high academic self-efficacy, to optimize the educational process being undertaken. Academic self-efficacy is an individual's belief in tasks and achieving academic achievement. 'Rapid counseling' is the provision of assistance with rapid counseling, and can be combined well with art. The purpose of this study was to determine the effectiveness of 'rapid counseling' with single-session music therapy (RC-SSMT) to increase academic self-efficacy in three students. This study is a quantitative experimental study with a one-group pre-test and post-test design. The subjects of this study were three students of the Department of Guidance and Counseling, Atma Jaya Catholic University of Indonesia (class of 2021), who experienced low academic self-efficacy based on questionnaires that had been filled out by the subjects. The data collection technique in this study was using interviews and questionnaires. This study used the Academic Self-Efficacy Scale (TASES) instrument which consisted of 28 items and had a validity of 0.893 and a reliability of 0.700. In the implementation of RC-SSMT, it can be effective in increasing academic self-efficacy with just one meeting session and can make the client independent with the "soundtrack of my life" that has been created together with the counselor during the counseling service so that when the client's academic is low again, the client only needs to listen to the song that has been created together with the counselor.